2004
DOI: 10.1029/2004gl021344
|View full text |Cite
|
Sign up to set email alerts
|

Decadal oscillation of spring rain in northern Taiwan

Abstract: [1] This study found that the spring (February -April) rainfall in northern Taiwan has fluctuated concurrently with the Pacific Decadal Oscillation (PDO) since the early 20th century. It is proposed that this fluctuation in spring rain is induced by the tropical sea surface temperature (SST) anomaly embedded in the PDO, which has been known to oscillate in opposite phase to the SST in the extra-tropical North Pacific. When the PDO index is positive (negative), the SST over the tropical Central-Eastern Pacific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 17 publications
5
43
0
1
Order By: Relevance
“…Other moving-window sizes (e.g., 21 years as adopted by Hung et al, 2004) have been tested as well, and the results are very similar 20 to (but less pronounced than) those presented herein.…”
Section: Regime Shifts In the Correlationsupporting
confidence: 65%
“…Other moving-window sizes (e.g., 21 years as adopted by Hung et al, 2004) have been tested as well, and the results are very similar 20 to (but less pronounced than) those presented herein.…”
Section: Regime Shifts In the Correlationsupporting
confidence: 65%
“…For instance, the spring rain in this region has a distinct characteristic; its rainfall is also very significant (Tian and Yasunari 1998). Some studies (Hung et al 2004;Jiang et al 2003) show that the spring rainfall over the WNP-EA has a strong interannual variation associated with El Niñ o-Southern Oscillation (ENSO) and an interdecadal variation associated with the Pacific decadal oscillation (PDO). Other studies (e.g., Chou 2004;Lau and Nath 2006;Wang et al 2000;Wu et al 2003;Zhang et al 1996Zhang et al ,1999Zhang and Sumi 2002) also showed the relationship between rainfall over the WNP-EA region and ENSO in different seasons.…”
Section: Introductionmentioning
confidence: 99%
“…1c). As such, total spring rainfall and its variability become more significant over northern Taiwan than southern Taiwan (Hung et al 2004). Jiang et al (2003) and Chen et al (2003) found that spring rainfall variability in Taiwan tends to be positively correlated with the preceding winter Niño-3 sea surface temperature (SST).…”
Section: Introductionmentioning
confidence: 99%